(untitled) (The Review of Diabetic Studies, 2025)
Antimicrobial resistance (AMR) is a critical global health crisis, requiring integrated surveillance strategies that transcend disciplinary boundaries. While microbiology remains the gold standard for pathogen identification and resistance profiling, radiology offers early, complementary indicators of infectious disease progression. The integration of radiological data with microbiological findings can enhance the timeliness, accuracy, and coverage of AMR surveillance systems. This review synthesizes current evidence on the radiology–microbiology interface, highlighting technological innovations, practical applications, and systemic challenges. Key barriers include interoperability gaps, lack of standardized imaging biomarkers for AMR, and data privacy concerns. Future directions include AI-driven integration, cross-disciplinary training, and global imaging-inclusive AMR databases.